If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -2 + 7x = 0 Reorder the terms: -2 + 6x + 7x = 0 Combine like terms: 6x + 7x = 13x -2 + 13x = 0 Solving -2 + 13x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 13x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 13x = 0 + 2 13x = 0 + 2 Combine like terms: 0 + 2 = 2 13x = 2 Divide each side by '13'. x = 0.1538461538 Simplifying x = 0.1538461538
| 5x+4/3x=6 | | (x^2)+5x-36=0 | | 5x-8y=-24 | | 5x+3/4x=6 | | 9D-7=7A | | a-2a+5= | | -5(17)+y=13 | | (x^2)-((x^3)/6) | | 4/5x-7x=6 | | 7x(x-3)(x+2)=0 | | 12x+3y=162 | | X/8+2=14 | | m+10-14m=-5 | | (3-3/2y)^2 | | -3x+3(5+13)=3 | | x-3+5x= | | 4k-28k=-49 | | 7x-4/5x=6 | | H/5+3=-6 | | 11(4-6x)+5(13y+1)=9 | | 3x+7-5x= | | 4k-14+3/c=21 | | 5h=2 | | 0=2m-18 | | -0.3f+1.3=4.8 | | -18/y+3 | | (x+16)+(x+22)=231 | | y^2-3y/y+3 | | 5(4x)-1/2x=234 | | 9h+4.5-7h+1.75= | | 6x+3x-3= | | 12+7C=103 |